Two‐Photon Absorption and Cell Imaging of Fluorene‐Functionalized Epicocconone Analogues. Issue 46 (25th July 2019) - Oger, Samuel; Schapman, Damien; Mougeot, Romain; Leleu, Stéphane; Lascoux, Noëlle; Baldeck, Patrice; Bénard, Magalie; Gallavardin, Thibault; Galas, Ludovic; Franck, Xavier
Abstract: Epicocconone1 is a natural chromophore isolated from the fungus Epicoccum nigrum that has shown applications in proteomics and fluorescent microscopy thanks to its unique pro‐fluorescence properties. The modification of the skeleton of the natural product by replacing the triene side chain by a fluorenyl scaffold can noticeably increase the fluorophore's absorption coefficient. The synthesis of the analogues of the natural product has been made possible by the use of a palladium‐catalyzed carbonylation reaction, allowing the construction of the β‐keto‐dioxinone key intermediate. Two‐photon absorption cross‐section measurements of the fluorenyl epicocconone analogues show a structure dependency with values ranging from 60 to 280 GM and live cell imaging show intense staining of intracellular vesicle‐like structures around the nucleus. Abstract : Modification of the skeleton of epicocconone by replacing the triene side chain by a fluorenyl scaffold can noticeably increase the fluorophore's absorption coefficient. Two‐photon absorption cross‐section measurements of the fluorenyl epicocconone analogues show a structure‐dependency with values ranging from 60 to 280 GM and live cell imaging shows intense staining of intracellular vesicle‐like structures around the nucleus (see figure).